Taiwan’s Appearance in the 18th Century Travelogue: Taking the Text of Histoire générale des voyages by Prévost - Chao-Ying Lee (Asian Studies, 2011)
There are a total of 15 volumes of Histoire générale des voyages written by Antoine François Prévost (1693–1763), which were published between 1746 and 1759. The 6th volume introduced China, in Section 4 of Chapter 1, the part of Fujian Province specially introduced geographic travelogues of Penghu and Taiwan. This thesis is an attempt to probe and criticize the historical European travelogue literature about China and Taiwan, specifically in terms of this Prévost’s travelogue volumes. What are the points of view presented, based on the reports of Jesuits and Protestants from Holland and England? What aspects of different traditional books did Prévost base his work on? Why? What kind of outlook on Taiwan was presented in their reports?